Implementasi Orhiba Di Mahad Al-Zaytun Pada Masa Pandemi Covid-19 - Sobirin Sobirin; Budi Santoso (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The Corona Virus Disease outbreak, also known as the Corona virus or Covid-19, is an acute respiratory syndrome disease that has spread to nearly every country in the world, infecting and killing many people. Education is one aspect of life that has been affected by this epidemic. The Indonesian government enforces online or online learning to prevent transmission. Nonetheless, an educational institution known as the Al Zaytun Campus continues to provide face-to-face instruction while adhering to health protocols and implementing numerous innovations. The innovations implemented are referred to as ORHIBA (New Life Order). The topic of this paper is therefore